Pemanfaatan E- Dakwah Sebagai Media Pengarusutamaan Moderasi Beragama Dalam Situasi Pandemi Covid 19 - Yunita Ratna Sari (Institut Agama Islam Negeri (IAIN) Curup, 2022)
E-da'wah as a medium for mainstreaming religious moderation is very helpful in the COVID-19 pandemic situation. Implementation of e-da'wah through social media and applications can make it easier for mad'u to receive religious moderation material.The purpose of this study is to explain the benefits of e-da'wah as an innovative medium for mainstreaming religious moderation in the current COVID-19 pandemic situation in Indonesia. The research uses a qualitative method which is a literature study. Collecting data through literature data, namely materials that are coherent with the object of the discussion in question. Sources of data using secondary data can come from various literature studies consisting of publications of national census and survey data, other government publications and the results of previous research. The results show that the e-dawah approach as a medium for mainstreaming religious moderation in the COVID-19 pandemic situation can be done through social media and applications. The social media that can be used are Facebook, YouTube and the TikTok application. E-dawah through social media and applications makes it easy for mad'u to access religious moderation material without being bound by space and time. The weakness of the implementation of e-da'wah through social media and applications is that mad'u cannot ask the preacher directly about religious moderation material so that the feedback is less than optimal.